Mathematical Communication Skills Included In The Content Of The Mathematics Textbook For The Third Grade Basic In The Syrian Arab Republic (An Analytical Study) - مرسل, هبة; رغداء نصور; خضر علي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The Current Research Aims To Determine The Availability Of Mathematical Communication Skills Within The Content Of The Mathematics Textbook Prescribed For The Third Grade In The Syrian Arab Republic. To Achieve The Objectives Of The Research, The Descriptive Approach Was Followed, And A List Of Mathematical Communication Skills (Main And Subsidiary) Was Prepared, Then A Content Analysis Form Was Designed, For The Purpose Of Analyzing Mathematics Book And Learn About The Mathematical Communication Skills Included In The Textbook And The Availability Rates Of Each Skill, The Results Of The Analysis Showed The Availability Of All Mathematical Communication Skills In Varying Percentages, As The Mathematical Written Expression Skill Came In First Place With A Percentage Of (45.19%), Followed By The Mathematical Reading Skill With A Percentage Of (26.51%), Then The Mathematical Representation Skill With A Percentage Of (16, 37%), While The Mathematical Oral Expression Skill Came At (8.36%), And The Mathematical Listening Skill Came At (3.55%), Based On The Previous Results, A Number Of Recommendations Were Presented, Most Notably Reconsidering The Content Of The Mathematics Textbook For The Third Grade, In Terms Of Including All Mathematical Communication Skills And Distributing Them Equally, With A Focus On The Skills That Achieved Low Percentages Within The Results Of The Analysis.